Promising practices for family involvement in schools - Hiatt-Michael, Diana B. (Family, school, community, partnership., 2001)
This volume will address major frameworks for understanding family involvement and government support of family involvement projects in the initial chapters. The following six chapters present a theoretical base for understanding school, family, and commu-nity partnerships and research supporting promising practices. Included within each chapter are examples of research in action, focusing on spe-cific interactive activities or programs designed to bring families and schools together. Such promising practices are organized into chapters dealing with two-way home-school communication, family literacy projects, school-site parent centers, parent- school collaborative governance, and family-school education programs spanning infancy through young adult-hood. The monograph concludes with a chapter on teacher preparation for work with family, school, and community partnership issues.Besides their research expertise, each author brings a unique back-ground as classroom teacher, parent, and community social advocate to their writing. Individually, most of us have spent our early professional years within the classroom, acquiring the value of connecting home with school for the benefit of the children. As parents and grandparents, we have advocated for parental interests within the school. As community advocates, we strive for collaborative communication across groups who serve children and their families. We invite you to share our passion for working with families and community groups within our schools.